Wielka Wenta Parialna na zakup dzownów - Stryszyk, Ignacy (1899-1957). (Kartuzy : [s.n.], 1947)
Afisz z grudnia 1947 r.
Keywords: Kartuzy (Polska) -- życie religijne -- 1945-1970.; Kartuzy (Polska) -- 1945-1970 -- druki ulotne